TRATAMIENTO NO QUIRÚRGICO DE UNA EXTENSA LESIÓN PERIAPICAL RELACIONADA CON UNA SOBREXTENSIÓN DE LA OBTURACIÓN CON CONOS DE GUTAPERCHA (2008)
A 18-year old male, the patient`s medical histories and systemic were al noncontributory. A clinical and radiographic examination revealed an extensive periapical lesion, intraoral swelling, sinus tract, related with over extended of the filling with gutta-percha cones to tooth 21, root canal wide and lack of apical constriction. The patient reported a previous history of dental trauma involving this quadrant. The diagnosis were suppurative chronic apical periodontitis of tooth 21. During root canal desobturation was drained Intracanal bloody serous exudate and yellow serous exudate. Following biomechanical preparation, a dressing of calcium hydroxide was applied and replaced three times over a period of 12 months. The clinical–pathological picture demonstrated resolution of the lesion during this period. An MTA white apical plug was placed in the apical portion of the root canal after one week, the canal were filled with gutta-percha. The 16-month clinical and radiographic examinations revealed normal bony contour and a significant resolution of the apical radiolucency. The aim of this article is report the repair of an extensive periapical lesion of endodontic origin, management with nonsurgical treatment.